Drawing of Piezoceramic Fibers and Ribbons using a Novel Alginate Gelation Method and Properties of Fiber and Ribbon-based Piezodevices - Alkoy, Sedat; Tekdas, A. Serkan; Tekel, Emre; Olukkent, Recep (Trans Tech Publications Ltd, 2012)
Piezoceramics are usually shaped into three dimensional bulk form using dry pressing or slip casting methods. However, certain applications require piezoceramics to be shaped in one dimensional fiber or two dimensional ribbon form. In this study, piezoceramic fibers and curved piezoceramic ribbons were fabricated using a novel alginate gelation method. Alginate is a natural linear polymer that is obtained from brown kelp. In the presence of multivalent cations, it forms ionic cross-links and gels in a three dimensional network form. In our study, gelation conditions of alginate containing aqueous slips of lead zirconate titanate based piezoelectric ceramic powders were investigated. Piezoelectric ceramic fibers and ceramic ribbons were prepared by sintering of gelled powders for transducer applications. Structural characteristics of these ceramics and electrical characteristics of piezodevices prepared from these ceramics were investigated and reported.
14th International Conference on Advances in Materials and Processing Technologies (AMPT) -- JUL 13-16, 2011 -- Istanbul, TURKEY
Keywords: Ceramics; piezoelectric; fiber; ribbon; alginate; piezocomposite; actuator